COVID-19 VACCINES: TARGETS, PRE-CLINICAL STUDIES, MECHANISMS OF ACTION, ADRS, AND ROLLOUT IN INDIA – A JOURNEY SO FAR - GOSAVI, DEVESH D; N SHINDE, CHETA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Coronavirus disease 2019 pandemic has been posing a serious threat to global public health till date. This calls for the development of effective treatment protocols, and most importantly, vaccines against the pathogen. Keeping these requirements in mind, we have pooled together, across broad domains of research, accounts on the leading efforts in the development of various vaccine candidates. It is apparent from our review of various studies that the efficacy of seemingly different techniques applied together, collaborative efforts coupled with rapid, timely dissemination of results has been the key behind successful vaccine development. The availability of curated databases has also been of great advantage. Furthermore, we have summarized in this article, the side effects of the various vaccines. We hope that this review will appeal the researchers and students as well as recent entrants in these research domains and the various studies described herein will inspire and be helpful for the advancement of public health.